L’evoluzione del sistema dell’innovazione in Italia tra norme, incentivi e nuove opportunità - Altobelli, Carla; Carnazza, Paolo (Argomenti, 2015)
The work aims to analyze the degree of innovation of the Italian productive system bringing out, on the basis of a series of researches, some lights and shadows. In particular, we focus on the evolution of innovative Italian firms during the years 2010-2012 in comparison with the European countries through a recent survey conducted by EUROSTAT. Then the study analyzes two distinct packages of facilitation measures: the first, adopted at the end of 2012, concerning innovative startups; the second (adopted at the end of March 2015) inherent the innovative SMEs. After having shown some "numbers" on the new world of innovative startups and provided an assessment of some specific facilitating measures in their favor, the work concludes with some reflections on future strategies that could make more effective the process started in recent years, strengthening the improvements already achieved, of which, however, we begin to “see” the first results.